ANALISIS KELAYAKAN FINANSIAL UNIT USAHA JASA MESIN PENANAM PADI (Rice Transplanter) DI KECAMATAN SEPUTIH RAMAN KABUPATEN LAMPUNG TENGAH - Bernadus Bagus Prabowo; Wan Abbas Zakaria; Teguh Endaryanto (Lampung University, 2018)
This study aims to analyze: the financial feasibility and the sensitivity of rice transplanter business unit. The location is purposively selected in Seputih Raman Subdistrict, Central Lampung Regency. This research uses a census method with 3 respondents owners of rice transplanters of two differences in machinery investment, i.e, the year of 2014 and 2015.. Data are analyzed quantitatively using measurement criteria for financial and sensitivity analysis. The results showed that the rice transplanter business unit is financially viable. The machine of rice planting business unit (rice transplanter) is still feasible despite the drop harvest area of 6.83%, the assumption of a decrease in rental rate machine of 5%, and the increase in operating costs of 3.85%.Key words: financial, rice transplanter, sensitivity